2018
DOI: 10.20473/fmi.v54i2.8866
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of 32.2 kDa MW Escherichia coli Pili Adhesin Isolated from Infertile Male Semen in Reproductive System

Abstract: ABSTRAKEscherichia coli (E. coli) motility (p=0.499), vitality (p=0.817) and morphology (p=0.176); between control and transuretral infection groups in motility (p=0.000), vitality (p=0.000) and morphology (p=0.000); and between control and both treatment groups in motility (p=0.001), vitality (p=0,000) and morphology (p=0.000

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…[37] PIP is a potential source of natural antioxidants that can control oxidative stress by inhibiting alpha-amylase and alphaglucosidase. [38] Several studies have shown that PIP obtained from long and black pepper has significant biological activities such as antioxidant, [39] anti-inflammatory, analgesic, [40] antihypertensive, [41] antitumor, [24] antimicrobial, [42] and antibacterial. [43] Selvendiran modulating lipid peroxidation and strengthening the antioxidant defense system.…”
Section: Discussionmentioning
confidence: 99%
“…[37] PIP is a potential source of natural antioxidants that can control oxidative stress by inhibiting alpha-amylase and alphaglucosidase. [38] Several studies have shown that PIP obtained from long and black pepper has significant biological activities such as antioxidant, [39] anti-inflammatory, analgesic, [40] antihypertensive, [41] antitumor, [24] antimicrobial, [42] and antibacterial. [43] Selvendiran modulating lipid peroxidation and strengthening the antioxidant defense system.…”
Section: Discussionmentioning
confidence: 99%
“…This study's working procedure consisted of identifying the K. pneumoniae 65.5 kDa pili protein using SDS-PAGE electrophoresis based on the Laemmli method (Blancher & Jones, 2003;Brunelle & Green, 2014;Laemmli, 1970;SCHÄGGER, 2003). After identification of the desired protein band, propagation and purification are then carried out and measured using the Kingsley method (Kingsley, 1939;Sukarjati et al, 2018). The purified protein was induced intraperitoneally in group 2 mice three times with an interval of 14 days.…”
Section: Designmentioning
confidence: 99%